The triangulated influence of electronic word of mouth (eWOM) information on consumer purchase intention: a conceptual paper / Irwan Ismail, Akmal Aini Othman and Muhammad Majid - Ismail, Irwan; Othman, Akmal Aini; Majid, Muhammad (UiTM Cawangan Johor, 2024)
In the contemporary of digital era, consumer decision-making processes have evolved significantly in response to the proliferation of information sources. This conceptual paper explores the intricate nexus between information credibility, valence information, information quality, and resultant consumer purchase intention across diverse industry domains. Recognizing the pivotal role of consumer perceptions in shaping buying decisions, this paper aims to elucidate the conceptual framework governing these variables. Through a comprehensive literature synthesis and theoretical analysis, this paper endeavours to delineate the interconnections among information credibility, valence content, and information quality, elucidating their collective influence on consumer decision-making. By proposing a conceptual framework that integrates these variables, this paper aims to offer a conceptual roadmap for understanding how consumers perceive and evaluate information credibility, react to valence content, and assess information quality, culminating in their purchasing behaviours across industry sectors. This conceptual exploration aims to lay the foundation for future empirical investigations and strategic business approaches, facilitating a deeper comprehension of the intricate dynamics guiding consumer behaviour in the digital age.